Presumption of sexual abuse in children and adolescents: vulnerability of pregnancy before 14 years - Ana Jéssica Cassimiro da Silva; Ruth França Cizino da Trindade; Larissa Lages Ferrer de Oliveira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to investigate the presumption of sexual abuse through the records of live births with mothers up to 13 years of age. Methods: this is a quantitative study, with an ecological design, carried out in Maceió, with data from the Brazilian Live Birth Information System from 2009 to 2017, based on Law 12,015/2009, on sexual crimes against the vulnerable, applying the presumption of violence in children under 14 years old. Results: nine hundred fifty-three births of children with mothers aged 10 to 13 years were recorded; 1.3% were reported as victims of sexual abuse; 20.3% declared to be married or living in a stable relationship. Records were concentrated in 04 neighborhoods, Guaxuma, Benedito Bentes, Tabuleiro do Martins, and Jacintinho. Conclusions: there was a prevalence of pregnancy and marriage in girls under 14 years of age and scarcity of reporting presumed sexual abuse by health professionals.